2020
DOI: 10.1021/acs.macromol.9b02695
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure Analysis of a Near-Ideal Polymer Network with Deuterium Label by Small-Angle Neutron Scattering

Abstract: Partially deuterated poly(ethylene glycol) (PEG) networks were fabricated by cross-linking a protonated four-arm PEG prepolymer (4hPEG) with a deuterated linear PEG (2dPEG) via a cross-end-coupling reaction. The structure of the resulting partially deuterated 4h-2dPEG networks and the corresponding non-cross-linked polymer solutions, i.e., a mixture of 4hPEG and 2dPEG homopolymers, was investigated in D 2 O solvent by small-angle neutron scattering (SANS) in a contrast-matched condition. The observed SANS prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…No scattering arising from the chains between HBSP junction points is observed, although they have the same contrast as the occluded PAAm chains around the HBSPs. [ 17 ] This seeming anomalism provides very helpful clues for the interpretation of SANS results. The scattering intensity is roughly proportional to the sixth power of characteristic dimension.…”
Section: Resultsmentioning
confidence: 99%
“…No scattering arising from the chains between HBSP junction points is observed, although they have the same contrast as the occluded PAAm chains around the HBSPs. [ 17 ] This seeming anomalism provides very helpful clues for the interpretation of SANS results. The scattering intensity is roughly proportional to the sixth power of characteristic dimension.…”
Section: Resultsmentioning
confidence: 99%
“…Representative SANS patterns obtained for gels typically lack peaks corresponding to strong correlations between strands or junctions due to the lack of long-range order and the amorphous character of the network (Figure ). Although it should be noted that scattering curves from charged gels typically do have a feature called the ”polyelectrolyte peak”, which corresponds to the correlation length ξ resulting from the like-charge repulsion of neighboring charged strands, SANS curves are usually fit with physical models to extrapolate structural parameters, similar to other techniques discussed in this review. Broadly, the high- q region characterizes polymer chains and the low- q region highlights larger length-scale network inhomogeneities.…”
Section: Network Structurementioning
confidence: 99%
“…In addition, the same temperature dependence between the gel and the monosequence profiles suggest that the change in the peak height was irrelevant to the sol–gel transition. By fitting the scattering profiles with a model function for star block copolymers under contrast‐matched conditions [ 53 ] (Figure 3a,b and Section S4.2, Supporting Information), we found that the difference in the peak height was attributed to the changes in the energy interaction between the PEG polymers and the water molecules at different temperatures. The estimated energy interaction parameters (χ) were displayed as a function of temperature (Figure 3c and Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%